Introduction of Inhaled Nitrous Oxide and Oxygen for Pain Management during Labour – Evaluation of Patientsʼ and Midwivesʼ Satisfaction - Dammer, U.; Weiss, C.; Raabe, E.; Heimrich, J.; Koch, M. C.; Winkler, M.; Faschingbauer, F.; Beckmann, M. W.; Kehl, S. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Effective pain management during labour is important because pain affects the birth experience. Epidural analgesia is effective but often it may not be possible; however, inhaled analgesia offers another option. Use of inhaled nitrous oxide and oxygen for pain management in labour is well established in obstetrics but is still not used much in Germany. This study aimed to investigate the acceptance of the inhaled analgesia of inhaled nitrous oxide and oxygen by midwives and pregnant women during labour.Material and Methods: In this observational study carried out between April and September 2013, a total of 66 pregnant women received inhaled nitrous oxide and oxygen during labour on request and after prior assessment of suitability. After the birth, all of the women and the responsible midwives were interviewed about their experience and satisfaction with the inhaled analgesia.Results: A statistically significant reduction of pain was achieved with nitrous oxide and oxygen. The inhaled analgesia was mostly used by women who refused epidural analgesia. The likelihood of using inhaled nitrous oxide and oxygen again was reported as higher for patients who tolerated it well (p = 0.0129) and used it in the second stage of labour (p = 0.0003) and when bearing down (p = 0.0008).Conclusion: Inhaled nitrous oxide and oxygen is an effective method for pain management during labour and is accepted well by women in labour and by midwives.
Keywords: perinatal; nitrous oxide; inhaled analgesia; pain management; satisfaction; labour